2003
DOI: 10.1086/376535
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Cycle Structured Intermittent versus Continuous Highly Active Antiretroviral Therapy for the Treatment of Chronic Infection with Human Immunodeficiency Virus: Effects on Drug Toxicity and on Immunologic and Virologic Parameters

Abstract: We evaluated the effect of long-cycle structured intermittent therapy (SIT; 4 weeks without highly active antiretroviral therapy [HAART] followed by 8 weeks with HAART) versus continuous HAART. The study was prematurely terminated to new enrollment because of the emergence of genetic mutations associated with resistance to antiretroviral drugs in 5 patients. After 48 weeks, there was no significant difference between groups in lipid, hepatic transaminase, and C-reactive protein levels in 41 patients. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 37 publications
5
47
2
Order By: Relevance
“…The difficulty of using immunologic parameters for blood to accurately predict the virologic outcome of STI is consistent with observations from human studies, where no or a variable correlation was observed between viral load markers and HIV-1-specific CD8 ϩ or CD4 ϩ T-cell responses that were augmented in blood during treatment interruptions (14,17,20,45,49).…”
supporting
confidence: 75%
See 1 more Smart Citation
“…The difficulty of using immunologic parameters for blood to accurately predict the virologic outcome of STI is consistent with observations from human studies, where no or a variable correlation was observed between viral load markers and HIV-1-specific CD8 ϩ or CD4 ϩ T-cell responses that were augmented in blood during treatment interruptions (14,17,20,45,49).…”
supporting
confidence: 75%
“…However, clinical trials found that the likelihood of STI to induce immunologic control of HIV replication was generally most favorable for patients who were started on HAART during acute infection, when the immune system was still relatively intact and when early treatment was able to lower the viral RNA set point after drug withdrawal (30,50). When treatment was started during chronic HIV infection, STI regimens were generally able to augment anti-HIV CD8 ϩ cell-mediated immune responses (to approximately pretreatment levels) but were less effective in restoring and maintaining HIV-specific CD4 ϩ cellular immune responses, and treatment interruptions generally led to a viral rebound to near pretreatment levels (17,20,44,45,(47)(48)(49)51).…”
mentioning
confidence: 99%
“…If successful, this strategy could limit drug toxicity and reduce treatment costs. 122 Although preliminary findings for this strategy were mixed in terms of benefits, [123][124][125] the recent early closure of the SMART trial was based on increased morbidity and mortality in the treatment interruption arm. 126 Thus, in the absence of clinical benefits, most investigators strongly discourage treatment interruptions except as needed to address treatment intolerance.…”
Section: Combination Antiretroviral Treatmentmentioning
confidence: 99%
“…Enrollment criteria for the SIT protocol, as previously described (21), were documented HIV infection with a CD4 ϩ T-cell count of Ͼ300 cells/mm 3 and plasma HIV RNA levels of Ͻ50 copies/ml during screening and Ͻ500 copies/ml for Ͼ6 months on a potent ART regimen comprised of a protease inhibitor (indinavir [IDV] or nelfinivir) combined with a nonnucleoside reverse transcriptase inhibitor (nevirapine [NVP] or efavirenz) and/or a nucleoside reverse transcriptase inhibitor (NRTI) (stavudine [d4T], didanosine, or lamivudine [3TC]). The study was designed for 90 patients randomly assigned to continue ART or receive seven cycles of 4 weeks without ART followed by 8 weeks with ART.…”
Section: Patient Characteristics Antiretroviral Treatment Regimens mentioning
confidence: 99%
“…The study was designed for 90 patients randomly assigned to continue ART or receive seven cycles of 4 weeks without ART followed by 8 weeks with ART. However, the study was prematurely terminated due to a high failure rate in the SIT arm after 26 patients in each arm were enrolled (21). Six of the 26 individuals from the treatment interruption arm voluntarily underwent a final cessation of ART after 92 weeks of SIT.…”
Section: Patient Characteristics Antiretroviral Treatment Regimens mentioning
confidence: 99%